Digital twins for smart cities : conceptualisation, challenges and practices - Wan, Li; Nochta, Timea; Tang, Junqing; Schooling, J. M. (ICE Publishing, 2023)
Digital twin technology has made great strides in the engineering and manufacturing sector over the past decade; however, there remains confusion around what a digital twin is and how they can be utilised successfully at a city scale. Digital Twins for Smart Cities provides conceptual clarity and practical guidance for supporting city-scale digital twin (CDT) development, outlining challenges, showcasing real-life CDT practices globally and offering socio-technical frameworks to compare CDT projects.